(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2022)
Brazilian coastal terraces contain abundant evidence that can be used to explain how the coastal plain evolved during the last 120k years. These studies include geochronology of marine sediments based on physical methods of dating by dosimetry, especially thermoluminescence. To determine terrace age by luminescence dosimetry methods is necessary to determine the exact mass fractions of 238U, 232Th and 40K. The values for these mass fractions are used to calculate the annual dose rate of ionizing radiation. In this context, in the present work, we studied eight marine sediment samples collected in the city of São Vicente on the coast of São Paulo state, Brazil, and determined the mass fractions of elements 238U, 232Th and 40K through instrumental neutron activation analysis (INAA) and γ-ray spectroscopy. The mathematical method of linear regression was used to evaluate the precision of the analytical methods. The results indicate excellent correlations with R2 values above 0.71. The resulting mass fractions can calculate dose rates in these sediments, thus contributing to their dating.